Approaches to Visual Culture and Religion - Uehlinger, Christoph (Method & theory in the study of religion, 2015)
Written from the point of view of a historian of religion\s, the article asks why the so-called “visual turn” has not left a major effect on the study of religion\s as an academic discipline and how things could be improved to that effect. It offers a synthetic account of earlier and contemporary involvements of scholars of religion and scholarly networks with images and visual culture, pointing to a general lack of sustained training and little exposure to relevant methodology and theory developed in relevant neighbouring disciplines. The author argues that the study of religion\s would benefit from increased attention to images and visual culture, emphasizing the potential of earlier (iconology in the Warburg-Panofsky tradition and the Groningen trajectory) as well as more recent approaches developed in Europe and the u.s., which theorize the visual in terms of visual culture, visual media, visual and scopic regimes, religious aesthetics and material religion.